The effect of different daily rations on the growth and total body composition of Volga pikeperch (Sander volgensis Gmelin 1788) under intensive culture conditions - Szabó, Gergely; Müller, Tamás; Molnár, Tamás; Sudár, Gergő; Zakęś, Zdzisław; Hancz, Csaba (Acta Agraria Kaposváriensis, 2009)
In the 6-week-long experiment 84 Volga pikeperch were introduced into the aquarium system working in a recirculation system. During the experiment the fish were fed a commercial pelleted fish feed once a day. The crude fat content of the feed was 11.5% and the crude protein content was 45%. During the experiment the feed was given to the fish in different amounts: the daily rations were 1%, 2% and 3% of the fish biomass. At the end of the experiment, samples of whole body of three fish by treatment were sent to the laboratory to determine th proximate chemical body composition. Feed conversion ratio showed values of 0.85–0.90 g/g. The amount of daily rations had a significant effect on the specific growth rate (S.G.R.) and on the amount of waste feed (P < 0.05), but no significant effect on the body composition. According to the results of this experiment the most suitable daily ration for the one-year old Volga pikeperch should be settled around 1.5–2% of fish biomass.